Analisis Implementasi Kebijakan Manajemen Berbasis Sekolah pada Sekolah Penggerak - Suprapti, Yuni; Dariyanto, Dariyanto; Supriyanto, Supriyanto (FKIP Universitas Wisnuwardhana, 2023)
This research aims to analyze the implementation of School Based Management (MBS) policies at the Driving School at SD Negeri 4 Ketindan, Lawang, Malang, East Java. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation and document analysis. The research results show that the implementation of SBM at SD Negeri 4 Ketindan has shown several significant successes, especially in increasing the active participation of all stakeholders, including principals, teachers, students and parents in the decision-making process. The implementation of this policy has also encouraged improvements in the quality of learning and more effective and efficient resource management. However, this research also identified several challenges, such as limited human resources and facilities that still need to be improved. Support from local governments and increasing the capacity of teaching staff are key factors in overcoming these challenges. Overall, this research provides important insights into the effectiveness and challenges in implementing SBM in Driving Schools, as well as suggesting strategic steps to improve the quality of education in elementary schools. It is hoped that the results of this research can become a reference for developing educational policies in the future.